Testing the Efficacy of Bankruptcy Prediction Models : A Study of Jet Airways - Dhingra, Deepika; Sharma, Seema; Ashok, Shruti (Indian Journal of Finance, 2024)
Purpose : This study aimed to test the efficacy of four prediction models – the Altman Z score model, the Zmijewski model, the Pilarski model, and the Springate model to examine their efficacy in forecasting the downfall of Jet Airways. Methodology : To assess the financial condition of Jet Airways from 2011–2018, scores of the Altman Z score model, Zmijewski model, Pilarski model, and Springate model were calculated. Further, to assess the statistical differences in means, the study used SPSS to conduct one-way ANOVA tests. Post hoc tests were also employed to identify the most accurate model. Findings : All four models were found to be efficient in predicting the bankruptcy of Jet Airways. According to the one-way ANOVA test findings, the Zmijewski model emerged as the most accurate model (M = 2.278); whereas, the Springate model displayed the least predictive accuracy (M = –0.103). Post-Hoc Games-Howell test results revealed that the Zmijewski model surpassed other models in predicting insolvency, while the Springate model exhibited the least predictive ability to predict the distress of Jet Airways (2011 – 2018). Practical Implications : Insights from this study are expected to assist aviation companies in identifying early signs of financial distress. The study will be useful for management to manage financial risks and safeguard long-term sustainability and competitiveness in the industry. Originality/Value : The results of the study were able to provide an accurate assessment of the financial position of Jet Airways during 2011–2018 and its impending bankruptcy. The idea of using the combination of all four models in the case of Jet Airways is a novel approach.